The structure and genre peculiarities of Thomson’s The Seasons - Kuosaitė, Elena (Literatūra, 1975)
Thomson’s poem is a heterogeneous work. A descriptive and reflective poem first and foremost, it contains elements of burlesque and parody too, and in some respects continues the tradition of the Georgic. The descriptive texture of the poem is interrupted by philosophical and moral considerations, scientific and geographical sections, narrative insets as well as by scenes from rural life. All this points to a fragmentic character of the poem, though it has a unifying basis too, which is the unity of thought and the author’s attempt to find the reflection of the same or similar ideas in different phenomena of nature. The Seasons is not a narrative poem, and its episodes are not linked with one another on the basis of cause and effect. They are grouped by means of association, on the principle of similarity and contrast, on their proximity in time and space, and according to their place in the system of the universe. A very important unifying element is the recurrent imagery that underlines the course of time and the constant movement which is essential to the life of nature. A peculiar structure of The Seasons was determined by the period of transition in which it was written. The classical doctrine was gradually losing its influence, while the new principles of art were not formed as yet. If measured by the criteria of the epic, the poem gives an impression of a loosely knit work of literature. But as a matter of fact this free and unconstrained form opened up new possibilities of poetic vision that was developed by the later generations of poets.